Estimation of Finite Population Mean in the Presence of Nonresponse on Both Study and Auxiliary Variables - Abubakari, Iddrisu; Jakperik, Dioggban; Nasiru, Suleman (Journal of Applied Statistics and Data Science, 2026)
The study investigated the challenge of estimating the expected value  of finite population of the main variable  using supplementary data from  under nonresponse. The proposed estimator was then compared with competing estimators. Analytical and empirical findings, demonstrate that the proposed ratio estimator, based on a third order approximation, exhibits higher efficiency than competing estimators, especially with large samples. The performance of the proposed ratio estimator, like other bias reduction estimators is enhanced for large samples.